Assessment of Agreement Among Evaluators in Scoring of Preclinical Full Metal Crown Preparation Using Global and Analytical Evaluation Methods - Nourelhouda Misurati; Noora Berhaim (AlQalam Journal of Medical and Applied Sciences, 2025)
It is essential to develop a reliable system for assessing preclinical tooth preparation in dental faculties. Many researchers have documented efforts to create dependable assessment systems for both laboratories and clinics. However, despite varying degrees of success, only a limited number of studies have employed an analytical approach to pinpoint the elements of the evaluation system that, with further refinement, could enhance reliability. This study aimed to compare the agreement among evaluators in two assessment methods: glance and grade (global) and checklist- and criteria-based assessment (analytical), for the evaluation of full metal crown preparation on the maxillary and mandibular first molars performed by 4th-year dental students. Sixty-nine fourth-year dental students and two faculty members from the fixed prosthodontics department, University of Tripoli, participated in this study. Each student prepared an ivorine tooth for the full metal crown on a maxillary or mandibular first molar on an upper or lower jaw dentoform. The two evaluators evaluated the work separately, and each evaluator first evaluated the preparation by glance and grade (global), and then by checklist and criteria-based assessment (analytical), the procedure was given a score on a 1 to 20 scale. The study revealed that, among the two evaluators, the level of intra-evaluator variability was not statistically significant. On the other hand, there were statistically significant differences in the level of inter-evaluator variability among evaluators evaluating full metal crown preparations with similar patterns of disagreement in both evaluation methods. It was concluded that among the two evaluators, there was inter-evaluator variability in pre-clinical evaluation using both global and analytical methods. On the other hand, the intra-evaluator variability was non-significant.